Is the Hong Kong Stock Market Asymmetrical in Behavior? - Venus Khim-Sen Liew; Chia, Ricky Chee Jiun; Syed Azizi Wafa Syed Khalid Wafa (Empirical Economics Letters, 2015)
This study uncovers that there exists asymmetrical market reaction on the positive and negative news by the TGARCH, EGARCH and EGARCH – M models. Thus, investors could use the calendar anomaly in terms of asymmetrical behavior information to avoid and reduce the risk when investing in the Hong Kong stock market.